Resistance to Sulphate and Acid Attack of Rice Husk Ash and Fly Ash Based Composite Cement (Dhaka University Journal of Science, 2023)
The current exploration work contains the preparation and examination of the properties of cement-based composite materials. Two kinds of composite materials specifically, Rice Husk Ash Composite Cement and Fly Ash Composite Cement were examined. Rice Husk Ash Composite Cement and Fly Ash Composite Cement was treated with Na2SO4 and HCl solution to check the resistance towards sulphate and acid attack respectively. Sulfate attack has been resolved in this work by estimating weight loss/gain of Ordinary Portland Cement (OPC) and the Composite Cements created from FA and RHA when plunged into 0.5 M and 0.75 M Na2SO4 solution. A loss in weight has been seen at the underlying stage i.e. Following 7 and 14 days when OPC is immersed in sulfate media, however, in the long run there was gain in weight of the composite made with OPC. The loss of weight occurred when the entire test sample is treated with 1.0 M HCl. Results on acid resistance and sulphate attack revealed that Composite cements are better acid resistant but more susceptible to sulphate attack. It was also observed that FAC composite is more susceptible to sulphate attack than RHAC composite. The Ca(OH)2 leaching tests indicate that Composite Cements are effective in reducing the amount of Ca(OH)2 leaching compared to pristine OPC.Dhaka Univ. J. Sci. 71(1): 49-55, 2023 (Jan)